2015
DOI: 10.1016/j.bbamem.2015.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neurosteroids on a model membrane including cholesterol: A micropipette aspiration study

Abstract: Amphiphilic molecules supposed to affect membrane protein activity could strongly interact also with the lipid component of the membrane itself. Neurosteroids are amphiphilic molecules that bind to plasma membrane receptors of cells in the central nervous system but their effect on membrane is still under debate. For this reason it is interesting to investigate their effects on pure lipid bilayers as model systems. Using the micropipette aspiration technique (MAT), here we studied the effects of a neurosteroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 64 publications
(86 reference statements)
0
3
0
Order By: Relevance
“…Both steroid hormones and neurosteroids, which are both found in the nervous system, are collectively referred to as neuroactive steroids and are important physiological regulators of nervous system functioning [23]. In particular, DHP controls reproductive functions, as well as glutamatergic and GABAergic neurotransmission [24], whereas isoallopregnanolone influences the lipid bilayer model system containing cholesterol [25,26]. In the brain, androgen molecules have been shown to regulate dendritic spine maturation [27,28], behaviour [29,30], neurite growth [31], neurogenesis and neuronal survival [32], apoptosis [33] and catecholamine production [34].…”
Section: Introductionmentioning
confidence: 99%
“…Both steroid hormones and neurosteroids, which are both found in the nervous system, are collectively referred to as neuroactive steroids and are important physiological regulators of nervous system functioning [23]. In particular, DHP controls reproductive functions, as well as glutamatergic and GABAergic neurotransmission [24], whereas isoallopregnanolone influences the lipid bilayer model system containing cholesterol [25,26]. In the brain, androgen molecules have been shown to regulate dendritic spine maturation [27,28], behaviour [29,30], neurite growth [31], neurogenesis and neuronal survival [32], apoptosis [33] and catecholamine production [34].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of enantiomeric steroids are important because enantiomers (unlike stereoisomers) have identical physico-chemical properties, including logP, and differ only in their rotation of polarized light (Alakoskela et al, 2007). Studies of NAS enantiomers provided the first strong evidence that NAS interact with chiral (likely protein) sites rather than exerting effects by changes in membrane properties, even though 5α-reduced steroids increase the liquid disordered state of membranes resulting in higher lateral membrane mobility (Balleza et al, 2015; Sacchi et al, 2015). Using fluorescent enantiomeric steroids, Chisari et al (2009) found that only NAS with the natural configuration of natural neurosteroids were able to potentiate GABA currents while both enantiomers accumulated identically in cell membranes and intracellular compartments.…”
Section: Effects Of Neurosteroids On Gabaarsmentioning
confidence: 99%
“…Micropipette aspiration technique was utilized to investigate the adhesive force of a single cell quantitatively. However, some of these studies have technical difficulties, such as the need for protein scaffolding of the cells to avoid membrane rupture when they are pulled by a nano- or micro-needle [ 6 , 7 ]. The first step of cell-surface adhesion was considered as the initial contact of cells with materials, in which cells were in round shape but no cytoskeletal change yet.…”
Section: Introductionmentioning
confidence: 99%